Pengaruh Model Pembelajaran Kooperatif Tipe TGT Terhadap Hasil Belajar Matematika Siswa - Muh Taufieq D (Tautologi: Journal of Mathematics Education, 2023)
The purpose of this study was to find out that the cooperative learning model of the Teams Games Tournament (TGT) type had a positive effect on the mathematics learning outcomes of class VIII MTS PP DDI As-Salman Allakuang. This type of research is a quasi-experimental study without a control class conducted in one group with a one group pretest and posttest design. The population of this study were students of class VIII MTS PP DDI As-Salman in the odd semester of the 2022/2023 academic year, which consisted of three classes, namely VIII.A, VIII.B and VIII.C. The sample of this study was students of class VIII.B, totaling 33 people who were obtained using the cluster random sampling technique. The research data was obtained using a research instrument in the form of a test of students' mathematics learning outcomes. The results showed that based on descriptive statistical analysis, the average value of the pretest was 43.39 and the posttest was 84.82 and inferential using the one sample t-test obtained a significant ρ = 0,001<α=0,05 this means H0 is rejected and H1 is accepted. So it can be concluded that the cooperative learning model of the Teams Games Tournament (TGT) type has a positive effect on the mathematics learning outcomes of class VIII MTS PP DDI As-Salman Allakuang.